Design and analysis of microstrip antenna with zig-zag feeder for wireless communication applications - Malik Jasim Farhan; Ali Khalid Jassim (Institute of Advanced Engineering and Science, 2021)
This paper is presented a microstrip antenna with a zig-zag feeder for wireless communication, it has a wideband frequency spectrum (2-14) GHz. The proposed antenna is designed with a zig zag feed line which gave a wideband frequency and acceptable gain (7.448-5.928) dB, this antenna has zig zag slots printed in the ground plane on a lower side of the dielectric substrate, a certain form tuning stub is used to increase the matching between the feeder in the top layer of the substrate and ground plane in the bottom, this stub has an elliptical slot to performance matching input impedance with the feed line. The feeding technique used to feed this antenna is a strip feed line of 50 Ω. Different types of techniques are used to enhance the bandwidth of this antenna to get a wideband suitable for the requirements of the UWB antenna such as adjust the feed point position of the feed line with a tuning stub. All the radiation properties of the presented antenna are tested such as bandwidth, radiation pattern, and, gain.